MEDIA FLASHCARD DAN PEMAHAMAN KESIAPSIAGAAN GEMPA BUMI SISWA SEKOLAH DASAR - Safitri, Andini; Pidi Mohamad Setiadi; Agnestasia Ramadhani Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the geographical conditionns of indonesia in the Ring of Fire area, which requires the systematic integration of disaster education from an early ago. Phenomena in the field show that elementary school students’ understanding of disaster mitigation is often still abstract and difficult to internalize due to delivery methods that tend to be monotonus and conventional. The main purpose of this study is to analyze the effectiveness of the use of flashcard media in improving cognitive understanding and building the mental readiness of grade IV elementary school students in facing the threat of earhquakes. The research method applied is qualitative descriptive to provide a systematic overview of the learning phenomenon at SD Negeri 1 Muktisari Banjar city. Data collection was carried out through participatory observation techniques, in- depth interview with homeroom teachers, and documentation studies. The validity of the data is ensured through triangulation and membercheck techniques to ensure the objectivity of the findings. The results of the study revealed that the use of flashcard media was able to bridge the limitations of space and physical simulation facilities in schools.The visual and interactive characterististics of these media have proven to be effective in accelerating the undertanding of techning terms as well as complex safety procedures through multisensory stimulation. The integration of this media in the learning procesess was found to be able to increase the active involvement of students compared to the use of conventional text. The positive impact resulting from this intervention is the formation of self- efficacy and a solid mental foundation in stundents. Through a clearer understanding of risk, students feel more empowered to take calmly and measurable self-rescue actions, so that the rist of psychological trauma due to disasters can be optimally suppressed from an early age.